Endüstriyel bir form olarak müstehcenliğin medyatik üretimi - Özden, Ufuk (My University, 2016)
Endüstriyel Bir Form Olarak Müstehcenliğin Medyatik Üretimi Cinselliğin metalaşması matbaanın Avrupa’da kullanılmaya başlanılmasından itibaren iletişim teknolojilerindeki yenilikleri takip etmiştir, 20’inci yüzyılda Batılı toplumlarda meydana gelen ekonomik ve sosyal değişimlerle beraber metalaşmış cinsellik pornografi biçimiyle ayrı bir endüstri yaratmıştır. Diğer taraftan pornografi endüstrisinin karlılığı ve metalarının hızla yaygınlaşması medya endüstrisini de etkisi altına almıştır. 1960’ların sonlarından itibaren yaşanan toplumsal hareketlerinde etkisiyle pornografi kapitalizmin daha gelişkin olduğu Batılı ülkelerde yasallaşmıştır. Pornografinin yasallaşmasını ve yaygınlaşmasını takiben ana akım medya endüstrileri yazılı, görsel-işitsel yayınlarının içeriklerinde pornografiye eş cinsel öğeler kullanmaya başlamıştır. Tiraj, reyting ve gişe kaygılarıyla cinselliğin metalaştırılması beraberinde kültürün pornografikleşmesini getirmiştir. Bu çalışmada kültürün pornografikleşmesi; medya ve cinselliğin metalaştırılması tarihsel bağlamında eleştirel ekonomi politik bir yaklaşımla ele alındı. stehcenlik, Medya

Mediatic Producton of Obscenity as an Industrial Form Commodification of sexuality has followed the innovations in communiation technologies. On one hand sexuality has developed as a distinct sector in media industry, on the other and mainstream industrial medias compatible with new communication tehchnologes have transformed obscenity to the additions of their product and content. In 20th century in line with the social and economic changes, commodified sexuality created a differentiated industry in the form of pornography. On the other side, profitabilty of the pornography industry and rapid prevalence of its commodities have affected media industry too. With the effect of the social movements have occured since the end of 1960s pornography was legalized in western countries where capitalism could be counted as more developed. Subsequent to legalization and prevalence of pornography, mainstream industries have started to use materails identical with pornography in the content of their written, visual and audial broadcasts. Commodification of sexuality caused by the anxiety of circulation, rating and finacial return accompanied with pornographication of culture. In this study, pornographication of culture, pornograhy industry in the context of commodification of media and sexuality were tried to be evaluated from the perspectives of immaterial labour and political economy of media. Key Words : Obscenity, Media
Keywords: Müstehcenlik, Medya